Surfactant protein-D predicts survival in patients with idiopathic pulmonary fibrosis - Barlo, N.P.; van Moorsel, C.H.M.; Ruven, et al., H.J.T. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: Idiopathic pulmonary fibrosis is a progressive interstitial lung disease with a high mortality rate. As lung transplantation is the only therapeutic option, it is important to predict survival. Objective: This study evaluates the clinical value of surfactant protein-D as a marker of prognosis in patients with idiopathic pulmonary fibrosis. Design: Surfactant protein-D was measured in serum of 72 patients and 305 healthy controls. The optimal cut-off level to define unfavourable prognosis was determined using a ROC analysis. A Cox’s proportional Hazards model was used to evaluate variables that were significant predictors of survival. Results: Serum levels of surfactant protein-D were significantly higher in patients than in controls. ROC analysis showed 460 ng/ml to be the optimal cut-off level to discriminate survivor from non-survivors after 1 year. Patients with high levels (> 460 ng/ml) had a median survival time of 13 months, compared to 67 months in the group with low levels (< 460 ng/ml). Surfactant protein-D showed to be a significant predictor of prognosis, even when corrected for age, sex, smoking, and lung function. Conclusion: The measurement of surfactant protein-D in serum of patients with idiopathic pulmonary fibrosis might be a clinically relevant tool to predict survival.